Role of service providers in ensuring effective service delivery in Mangaung Metropolitan Municipality - Ruwanika, Joseph M.; Maramura, Tafadzwa C. (Taylor and Francis Group, 2024)
The purpose of this article is to determine the role of service providers in Mangaung Metropolitan Municipality (MMM) in ensuring effective service delivery. The absence of transparency, accountability, and proper and trustworthy structures and procedures in public procurement leads to corruption and abuse of resources, costing the nation its livelihoods, when services are ill-delivered. Therefore, service delivery has become increasingly important as a driving force in the South African economy. However, there has been limited research done in the role of service providers in ensuring effective service delivery. The article is a case study research design and data were gathered using semi structured interviews at the Supply Chain Management Department at the MMM based on a snowball sampling technique. The article reveals the role of service providers in ensuring effective service delivery in the MMM. It also found that there needs to be training to minimize corruption and poor service delivery within the public sector. Furthermore, the study recommended that service providers should monitor projects and they should perform their duties and responsibilities in terms of specification to ensure efficient and effective service delivery. The participants recommended that to enhance service delivery, there is a need to hire people in supply chain management with the capacity, skills, and knowledge to do the job. 𝗜𝗠𝗔𝗣𝗖𝗧 𝗦𝗧𝗔𝗧𝗘𝗠𝗘𝗡𝗧 The processes of public procurement through which the public sector and governments obtain required goods, works and services can be used to uphold certain guidelines. Therefore, to ensure efficient, effective and economic service delivery, there is a need to shift away from inner observing, bureaucratic structures, procedures, and approaches and a look into innovative ways of working, which put the requirements of the community first, is better, quicker, and more receptive to the citizens requests. It also implies a broad shift in the method that services are provided. The article reveals the role of service providers in ensuring effective service delivery in the MMM. It also acknowledges that there needs to be training to minimize corruption and poor service delivery within the public sector. Furthermore, service providers should monitor projects and they should perform their duties and responsibilities in terms of specification to ensure efficient and effective service delivery.
Keywords: Service delivery; supply chain management public service; effective commodities